THE USE OF SOLID AND LIQUID MEDIUM TO STUDY THEEFFECTS OF HEAVY METALS ON THE GROWTH OF CANDIDA ALBICANS - iMakia M.Al-Hejuje; Mohammed H.Khudor (Basrah Journal of Veterinary Research)
Sabouraud's dextrose (solid and liquid) medium has been used to examine the response of Candida albicans to Cobalt , Nickel , Silver , Copper and Lead in three doses per each (10 , 25 and 50) mg/l in different exposure periods . In the solid medium the number of colonies was not effected by all metals ions , except Ag ions'(25 and 50) mg/l which completely inhibited the colonies numbers . In the liquid medium the effect of these metals on the growth was in the following sequence Co , Ni . Ag , Cu and Pb respectively: ' Most elements studied: showed increase in- the ‘inhibition effect on the growth with A increasing the ions concentration in the medium , whilethe inhibition effect decreased with the increasing periods of exposure